Social Media in Trinidad : Values and Visibility - Sinanan, Jolynna (Book collections on Project MUSE., 2017)
Drawing on 15 months of ethnographic research in one of the most under-developed regions in the Caribbean island of Trinidad, this book describes the uses and consequences of social media for its residents. Jolynna Sinanan argues that this semi-urban town is a place in-between: somewhere city dwellers look down on and villagers look up to. The complex identity of the town is expressed through uses of social media, with significant results for understanding social media more generally. Not elevating oneself above others is one of the core values of the town, and social media becomes a tool for.